2023
DOI: 10.1002/ags3.12711
|View full text |Cite
|
Sign up to set email alerts
|

Essential updates 2021/2022: Perioperative and surgical treatments for gastric and esophagogastric junction cancer

Abstract: In recent years, important clinical trials for gastric cancer (GC) and esophagogastric junction cancer (EGJC) have been reported, changing the strategies of surgical and perioperative treatment. Although laparoscopic gastrectomy has already been shown to be effective for early‐stage cancer, recent evidence from both Asia (JLSSG0901, CLASS‐01 and KLASS‐02) and Europe (LOGICA and STOMACH trials) has demonstrated that it is useful for advanced GC. Robotic surgery has been rapidly gaining popularity in recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 76 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Minimally invasive surgery for EGJC has the advantage of allowing both the surgeon and the assistant to perform manipulations with a clear, magnified surgical view, even in the narrow, deep surgical field of the lower mediastinum. 33) Some studies on Siewert type II EGJC showed that the laparoscopic transhiatal approach resulted in a better prognosis and the harvesting of a significantly larger number of lymph nodes compared with the open approach 34 , 35) ; however, no RCTs have compared the minimally invasive and open transhiatal approaches for EGJC, and the usefulness of the former is not clear. In particular, a subgroup analysis of a Japanese multicenter prospective study showed a relatively high anastomotic leakage rate (19.0%) with the laparoscopic transhiatal approach for EGJC, indicating that reconstructive procedures with a narrow surgical view in the lower mediastinum remain technically difficult ( Table 4 ).…”
Section: Surgical Treatment For Egjcmentioning
confidence: 99%
“…Minimally invasive surgery for EGJC has the advantage of allowing both the surgeon and the assistant to perform manipulations with a clear, magnified surgical view, even in the narrow, deep surgical field of the lower mediastinum. 33) Some studies on Siewert type II EGJC showed that the laparoscopic transhiatal approach resulted in a better prognosis and the harvesting of a significantly larger number of lymph nodes compared with the open approach 34 , 35) ; however, no RCTs have compared the minimally invasive and open transhiatal approaches for EGJC, and the usefulness of the former is not clear. In particular, a subgroup analysis of a Japanese multicenter prospective study showed a relatively high anastomotic leakage rate (19.0%) with the laparoscopic transhiatal approach for EGJC, indicating that reconstructive procedures with a narrow surgical view in the lower mediastinum remain technically difficult ( Table 4 ).…”
Section: Surgical Treatment For Egjcmentioning
confidence: 99%
“…Gastric cancer is the fourth leading cause of cancer deaths worldwide [ 1 ]. The only curative treatment for gastric cancer is surgical resection [ 2 4 ]. Patients with gastric cancer sometimes have para-aortic lymph node metastases or bulky lymph node metastases located along the main arteries such as the celiac, splenic, common, or proper hepatic arteries.…”
Section: Introductionmentioning
confidence: 99%
“…In East Asian countries like Japan and Korea, where screening program is widely conducted, treatment typically involves D2 gastrectomy followed by adjuvant chemotherapy, even though neoadjuvant therapy is becoming more common. Conversely, western countries put more focus on neoadjuvant-adjuvant therapy in combination with surgery ( Suh and Yang, 2015 ; Allemani et al, 2018 ; Yanagimoto et al, 2023 ). Despite the significant progress in the therapeutic strategies and surgical techniques, there remains a rather high risk of recurrence and metastasis in resectable cases, with the 5-year survival rates showing a substantial decline in patients beyond stage II ( Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%